Analysis of the effect of metal ions on the ability of Xylanase to hydrolyze wheat bran by molecular dynamics simulations - Hou, Mingrui; Liang, Chuanqi; Fei, Yanan; Yang, Dan; Zhang, Ningjing; Lu, Yujie; Wang, Lei; Xing, Zhiqiang; Zhao, Zongpei (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Wheat bran is the main by-product of wheat processing, containing about 30% pentosan and 0.4%–0.7% ferulic acid. Wheat bran is the main raw material used to prepare feruloyl oligosaccharides by hydrolysis of Xylanase, we discovered that the ability of Xylanase to hydrolyze wheat bran could be affected in the presence of different metal ions. Methods: In the present study, we have probed the effects of different metal ions on the hydrolysis activity of Xylanase on wheat bran and tried to analyze the effect of Mn2+ and Xylanase by molecular dynamic (MD) simulation. Results: Our results suggested that Mn2+ had improved the Xylanase hydrolyzing wheat bran to obtain feruloyl oligosaccharides. Particularly when the concentration of Mn2+ reached 4 mmol/L, the optimal product has been obtained 2.8 times higher to compare with no addition. Through the MD simulation analysis, our results reveal that Mn2+ can induce structural change in the active site, which enlarges the substrate binding pocket. The simulation results also revealed that the addition of Mn2+ resulted in a low RMSD value compared with the absence of Mn2+ and helped stabilize the complex. Conclusion: Mn2+ could increase the enzymatic activity of Xylanase in the hydrolysis of feruloyl oligosaccharides in wheat bran. The finding could have significant implications for the preparation of feruloyl oligosaccharides from wheat bran.